2015
DOI: 10.1001/jamadermatol.2014.3837
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Efficacy of Patient-Initiated Mobile Teledermoscopy for Short-term Monitoring of Clinically Atypical Nevi

Abstract: Results from this pilot study suggest that teledermoscopy is feasible and effective as a method for short-term monitoring of clinically atypical nevi. The implementation of teledermoscopy can potentially enhance patient convenience, optimize physician scheduling, and promote efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 26 publications
(46 reference statements)
1
90
0
1
Order By: Relevance
“…There was a predominance of female sex in six studies, 5,36,40,45,46,50 male predominance in two studies, 41,43 and no information about sex in nine studies. Participants' age also varied, ranging from infants to elderly patients.…”
Section: Study Qualitymentioning
confidence: 91%
See 3 more Smart Citations
“…There was a predominance of female sex in six studies, 5,36,40,45,46,50 male predominance in two studies, 41,43 and no information about sex in nine studies. Participants' age also varied, ranging from infants to elderly patients.…”
Section: Study Qualitymentioning
confidence: 91%
“…7,36,37,40,[45][46][47][50][51][52] Twelve studies analyzed the reliability by kappa statistics. 5,36,[38][39][40][41][42][44][45][46]48,50 From these, one study compared teledermatology and FTF diagnosis to histopathological results, 39 one compared both groups to teledermatology and FTF diagnosis to the definitive diagnosis, 40 all the others considered FTF consultation as standard reference without histopathological confirmation for the diagnosis. In two studies focusing on reliability, teledermatology was used for advising another medical provider.…”
Section: Study Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Second, patients harboring these nevi should receive tailored counseling regarding the expected size evolution of these nevi to facilitate skin self-examination, prevent unnecessary skin biopsy, and possibly mollify patient anxiety. Although follow-up traditionally is performed in the office setting, Wu et al 16 recently showed that patients are capable of acquiring follow-up dermoscopic images and electronically submitting them to a teledermoscopist for evaluation. Nevus growth is a dynamic process influenced by a complex interplay of genetic and environmental factors.…”
Section: Research Original Investigationmentioning
confidence: 99%